Nitric Oxide and Other Molecules: Molecular Modeling and Low-frequency Exploration Using the Murchison Widefield Array - Tremblay, C.D.; Gray, M.D.; Hurley-Walker, Natasha; Green, J.A.; Dawson, J.R.; Dickey, J.M.; Jones, P.A.; Tingay, Steven; Wong, O.I. (IOP Publishing Ltd, 2020)
We present new molecular modeling for 14NO and 15NO and a deep, blind molecular line survey at low radio frequencies (99-129 MHz). This survey is the third in a series completed with the Murchison Widefield Array (MWA), but in comparison with the previous surveys, uses 4 times more data (17 hr versus 4 hr) and is 3 times better in angular resolution (1′ versus 3′). The new molecular modeling for nitric oxide and its main isotopologue has seven transitions within the MWA frequency band (although we also present the higher-frequency transitions). Although we did not detect any new molecular lines at a limit of 0.21 Jy beam-1, this work is an important step in understanding the data processing challenges for the future Square Kilometre Array and places solid limits on what is expected in the future of low-frequency surveys. The modeling can be utilized for future searches of nitric oxide.